PATHOTYPE DELINEATION IN RHIZOCTONIA SOLANI ANASTOMOSIS GROUP ONE CAUSING FOLIAR BLIGHTS IN MUNGBEAN1 - JAI SINGH; K. K. MISHRA; A. K. CHAUBEY (The Bioscan, 2014)
Web blight caused by Rhizoctonia solani anastomosis group 1, intraspecific group IB was the major pathotype in Eastern Uttar Pradesh and causing an average yield loss up to 40% in both the years. Web blight pathotype differs from aerial blight which was initially thought to be misnomer. Isolates causing web blight of mungbean fused only with tester isolates AG-1IA and AG-1IB but not with AG-1IC. All isolates identified in samples from various locations were R. solani AG-1. Isolates of R. solani collected from mungbean causing web blight symptoms, exhibited C2 reaction (imperfect fusion or killing reaction) with AG-1IA and AG-1IB tester isolates and C1 type reaction with AG-1IC. Therefore, the web blight isolates were identified to belong to AG-1IB where as aerial blight isolates belong to AG -1-IA. Sneh et al.(1996), reported that R. solani AG-1IC causes damping off and crown root rot in Buckwheat, Carrot, Soybean, Flax and Pine, hence, it is clearly indicated that aerial blight isolates of mungbean have no possibility to belong to AG-1IC.